The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s40820-019-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Silica-Based Drug Delivery System for Spinal Cord Injury Therapy

Abstract: Acute inflammation is a central component in the progression of spinal cord injury (SCI). Anti-inflammatory drugs used in the clinic are often administered systemically at high doses, which can paradoxically increase inflammation and result in drug toxicity. A cluster-like mesoporous silica/arctigenin/CAQK composite (MSN-FC@ARC-G) drug delivery system was designed to avoid systemic side effects of high-dose therapy by enabling site-specific drug delivery to the spinal cord. In this nanosystem, mesoporous silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In addition, an increase of IL-17 concentration can result in the increase in the size of a lesion after SCI. Study has shown that reducing the expression of IL-17 and IL-17-related inflammatory factors can protect neurons and promote recovery after SCI [33]. In the PPI network developed in this study, the top 10 high-degree hub nodes (Ccl4, Ppbp, Cxcl13, Ahsp, Ccl5, Alas2, Npy, Gng13, Ccl2, and Hba2.)…”
Section: Discussionmentioning
confidence: 88%
“…In addition, an increase of IL-17 concentration can result in the increase in the size of a lesion after SCI. Study has shown that reducing the expression of IL-17 and IL-17-related inflammatory factors can protect neurons and promote recovery after SCI [33]. In the PPI network developed in this study, the top 10 high-degree hub nodes (Ccl4, Ppbp, Cxcl13, Ahsp, Ccl5, Alas2, Npy, Gng13, Ccl2, and Hba2.)…”
Section: Discussionmentioning
confidence: 88%
“…Silicon coming from the functionalized MSNs was detected in both CTX and SC tissues, as observed in a recent study. 36 In all cases, concentrations above 2300 ppm were observed ( Table S1 ), pointing to the fact that the tested materials were able to reach the target tissues and act as encapsulators or carriers of the combination of drugs leptin and pioglitazone and were able to cross the BBB.…”
Section: Resultsmentioning
confidence: 89%
“…35 Thus, to the best of our knowledge, we report one of the first examples of effective treatment of ALS by silica-based drug delivery of nanomaterials to biological targets in the central nervous system. 30,36 Our results open up promising new possibilities in the fight against the symptoms and fatal progression of this disease.…”
Section: Introductionmentioning
confidence: 82%
“…Nanomaterials have higher efficiency and certain pertinence because they more directly regulate the imbalance of homeostasis. Therefore, introducing NPs and nanotechnology may be a new therapeutic strategy for maintaining the balance of the microenvironment 207 .…”
Section: Nanotechnology-related Strategies Ameliorate Covid-19mentioning
confidence: 99%